Stress-strain and penetration characteristics of clay modified with crumb rubber - Vijayasimhan, Sivapriya (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Waste disposal has become a serious issue worldwide due to the huge amount of by-products generated by refineries and smelting industries that threat the environment if they are disposed inefficiently. Development of roads leads to a large usage of vehicles and, hence, a large amount of rubber waste (i.e., from tyres). Given that storing this material pollutes the environment, its recycled reused is currently trending. Various percentages of crumb rubber (0, 10, 15, 20, 30, 40 and 50) were mixed with highly and low compressible clay to understand the strength and penetration characteristics of the modified clay. Additionally, the thickness reduction of the pavement layer that reduces construction costs was visualize.